The effects of price, brand image, and product quality on customer loyalty and repurchase (a study case on customers of Walls products) - Prasetyo Harisandi; Purwanto Purwanto (President University, 2022)
Intense industry competition, as well as rapid changes and efforts to retain customers, are competitive goals and scarce resources for the ice cream industry. Price, brand image, and product quality implementation increases customer loyalty and is taken into account in the subsequent purchasing process. The goal of this study was to look at how price, brand image, and product quality affect customer loyalty and repurchase intent. A sample of 130 people who buy Walls brand ice cream products were surveyed. SEM (Structural Aquation Model) is the data analysis method used in this study to test the hypothesis. The results of this study conclude that price, brand image, and product quality have a positive effect on customer loyalty, and customer loyalty also has a positive effect on repurchase intentions. If the loyalty of the majority of customers has the strongest impact on repurchase intention.